JURISDICTIONAL REVIEW OF THE CRIME OF ASSOCIATED MURDER WHICH CAUSES THE DEATH OF THE VICTIMS ARTICLE 170 of the Criminal Law Code (Case Study of Decision Number: 118/Pid.B/2020/PN Tgl) - Tobondo, Yuyun Alfasius (FOCUS: Jurnal of Law, 2024)
Joint persecution or beating is a criminal offense involving more than one person. This research aims to understand the application of the law against maltreatment that causes death and the judge's consideration in imposing sanctions. Using a normative juridical approach, this research collects primary and secondary data through field and literature studies, analyzed descriptively qualitatively. The results showed that in case 118/Pid.B/2020/PN.Tgl, the defendant was charged under Article 338 of the Criminal Code Jo Article 55 paragraph (1) to 1 of the Criminal Code and Article 170 paragraph (1), (2) to 3 of the Criminal Code. The facts of the trial proved the elements of the criminal offense in the subsidiary charges, and there were no justifications or excuses for the defendant, so he must be held criminally responsible. The judge considered the principle of "For the sake of justice based on God Almighty" as well as the facts of the trial and the charges of the public prosecutor. In this case, the judge handed down a sentence of seven years, which was lighter than the eight years demanded by the prosecutor.